Fundamentals of forensic DNA typing - Butler, John M. (Amsterdam : Academic Press, 2010)
From the Publisher: John Butler, bestselling author of Forensic DNA Typing, now applies his expertise on the subject of DNA analysis into an introductory textbook. Fundamentals of Forensic DNA Typing walks students step-by-step through the DNA analysis process beginning with collection of evidence at a crime scene to the statistical interpretation of the results. Also included are brief discussions of such news worthy topics as victim identification from the September 11, 2001 attacks, the identification of the remains of the Romano vs, the last Russian Royal family, and the O.J. Simpson case. New applications, such as genetic genealogy and tracing domestic pet hairs to perpetrators, are also detailed. With its clear and understandable style and extensive list of online ancillaries and study aids, this textbook will make the subject accessible to students in forensic science courses worldwide. Includes a glossary with over 400 terms for quick reference of unfamiliar terms as well as an acronym guide to decipher the DNA dialect; Continues in the style of Forensic DNA Typing, 2e, with high-profile cases addressed in D.N.A. Boxes. "Data, Notes & Applications" sections throughout; Ancillaries include: instructor manual Web site, with tailored set of 1000+ PowerPoint slides (including figures), links to online training websites and a test bank with key.
Foreword -- Introduction -- Acknowledgments -- About the author -- Chapter 1: Overview and history of DNA typing -- Chapter 2: Basics of DNA biology and genetics -- Chapter 3: Historical methods -- Chapter 4: Sample collection, storage, and characterization -- Chapter 5: DNA extraction -- Chapter 6: DNA quantitation -- Chapter 7: DNA amplification (the polymerase chain reaction) -- Chapter 8: Short tandem repeat markers -- Chapter 9: Fundamentals of DNA separation and detection -- Chapter 10: STR genotyping and data interpretation -- Chapter 11: Statistical interpretation: evaluating the strength of forensic DNA evidence -- Chapter 12: DNA databases -- Chapter 13: Quality assurance -- Chapter 14: Forensic challenges : degraded DNA, mixtures, and LCN -- Chapter 15: Additional loci and nonhuman DNA testing -- Chapter 16: Lineage markers : Y chromosome and mtDNA testing -- Chapter 17: Applications of DNA typing -- Chapter 18: Future trends -- Appendix 1: Glossary of terms -- Appendix 2: Useful web sites -- Appendix 3: Probability and statistics -- Index.
Includes bibliographical references and index.
Keywords: DNA FINGERPRINTING